Experimental validation of a novel compact focusing scheme for future energy-frontier linear lepton colliders. - White, G; Ainsworth, R; Akagi, T; Alabau-Gonzalvo, J; Angal-Kalinin, D; Araki, S; Aryshev, A; Bai, S; Bambade, P; Bett, DR; Blair, G; Blanch, C; et al. (2014)
A novel scheme for the focusing of high-energy leptons in future linear colliders was proposed in 2001 [P. Raimondi and A. Seryi, Phys. Rev. Lett. 86, 3779 (2001)]. This scheme has many advantageous properties over previously studied focusing schemes, including being significantly shorter for a given energy and having a significantly better energy bandwidth. Experimental results from the ATF2 accelerator at KEK are presented that validate the operating principle of such a scheme by demonstrating the demagnification of a 1.3 GeV electron beam down to below 65 nm in height using an energy-scaled version of the compact focusing optics designed for the ILC collider.